(untitled) (Dhaka University Journal of Linguistics, 2011)
This article discusses Krashen’s Monitor Model and the attendant five hypotheses. Since its 1977 publication, Krashen, through a series of revisions, have tried to explain the way learners acquire a second language. This article closely looks at his basic premises and the criticism they have generated to better understand both the Monitor Model and its various lacunae and biases. Key words: Affective Filter; Krashen; Language Acquisition Device (LAD); Monitor Model; Second Language Acquisition (SLA). DOI: 10.3329/dujl.v2i4.6903 Dhaka University Journal of Linguistics Vol.2(4) August 2009 pp.139-146